Voices and challenges of marginalized and vulnerable groups in urban informal settlements in Nairobi, Kenya: building on a spectrum of community-based participatory research approaches - Karuga, Robinson; Kabaria, Caroline; Chumo, Ivy; Okoth, Linet; Njoroge, Inviolata; Otiso, Lilian; Muturi, Nelly; Karki, Jiban; Dean, Laura; Tolhurst, Rachel; Steege, Rosie; Ozano, Kim; et al. (Frontiers in Public Health, 2023)
Urbanization is rapidly increasing across Africa, including in Nairobi, Kenya. Many people, recent migrants and long-term residents, live within dense and dynamic urban informal settlements. These contexts are fluid and heterogeneous, and deepening the understanding of how vulnerabilities and marginalization are experienced is important to inform pointed action, service delivery and policy priorities. The aim of this paper is to explore vulnerabilities and marginalization within Korogocho and Viwandani informal settlements in Nairobi and generate lessons on the value of a spectrum of community based participatory research approaches for understanding health and well-being needs and pinpointing appropriate interventions. In the exploratory stages of our ARISE consortium research, we worked with co-researchers to use the following methods: social mapping, governance diaries, and photo voice. Social mapping (including the use of Focus Group Discussions) identified key vulnerable groups: marginalized and precarious child heads of households (CHHs), Persons with disability who face multiple discrimination and health challenges, and often isolated older adults; and their priority needs, including health, education, water and sanitation. The governance diaries generated an understanding of the perceptions of the particularly vulnerable and marginalized informal settlement residents regarding the various people and institutions with the power to influence health and wellbeing; while photo voice highlighted the lived experiences of vulnerability and marginality. Understanding and responding to fluid and intersecting marginalities and vulnerabilities within growing urban informal settlements is particularly critical to achieving inclusive urbanization, where no one is left behind, a theme central to the Sustainable Development Goals and Kenya’s Vision 2030.